The challenge of demonstrating the impact of research beyond traditional mechanisms - Marcella, R.; Lockerbie, H.; Cameron, Roslyn (ECRM, 2015)
The concept of ‘impact’ in academia is a focus of not only research councils but also of nationwide institutional research evaluations. In the UK, it is necessary for academics and their institutions to not only conduct research which has real impact, but to provide evidence of impact beyond academic bibliometrics. This includes evidence of impact on industry, government, wider communities and beyond (REF 2011). In Australia, the Excellence in Research for Australia (ERA) requirements for the 2015 reporting indicate research outputs, income, and both applied and esteem measures, are to be used to assess the excellence of research activity (Australian Research Council 2014). In addition the Australian Research Council (ARC) has piloted a new tool, the Excellence in Innovation for Australian (EIA) as a potential companion exercise alongside ERA to measure impact. This paper provides an overview of impact definitions in the UK and Australia, drawing on guidance from research councils and the UK’s Research Excellence Framework (REF). The research assessment environments in both countries are also described. The challenges of research assessment and the introduction of impact into this are discussed.The analysis of four impact case studies, published by the Economic and Social Research Council (ESRC) from the UK, is presented and discussed, and one author offers personal reflections into the construction of an impact case study for REF 2015. The paper ends with discussions on best practice, identified through critical examination of existing frameworks and case studies, on how to incorporate impact into research design ab initio, including anticipated and unanticipated impacts, as well as the collection of evidence to demonstrate these. At a time when the importance of impact is growing in the demonstration of institutional and personal research excellence and esteem, the paper contributes to an area of very significant dialogue and reflection for the research community, of value to both early career and senior researchers.